Can a weekend of controlled hypoxia restore hormonal balance? A novel approach to stress recovery in aviation professionals - Jose Francisco Tornero-Aguilera; Francisco José Martin-Gomez; Manuel Martinez-Taranilla; Alejandro Rubio-Zarapuz; Alexandra Martín‐ Rodríguez; Alexandra Martín‐ Rodríguez; Vicente Javier Clemente-Suárez; Vicente Javier Clemente-Suárez (Frontiers in Physiology)
BackgroundAviation professionals experience chronic stress due to prolonged work hours, irregular schedules, and exposure to altitude-related physiological challenges, leading to dysregulation of the hypothalamic-pituitary-adrenal (HPA) axis. Controlled hypoxia has been proposed as a potential strategy for modulating stress responses and enhancing recovery.ObjectiveThis study aimed to investigate the effects of a weekend of controlled normobaric hypoxia on key hormonal markers, including cortisol, prolactin, testosterone, and DHEA-S, in pilots and flight attendants.MethodsA within-subject experimental design was used with 10 participants (6 pilots, 4 flight attendants) exposed to two 12-hour sessions of normobaric hypoxia (simulated altitude: 3,500–4,000 m) during their designated rest period. Blood samples were collected at three-time points: baseline, pre-hypoxia, and post-hypoxia, and analyzed for hormonal changes.ResultsProlactin levels significantly increased post-intervention, indicating a neuroendocrine stress response. Cortisol levels showed a moderate decrease, suggesting potential stress adaptation. Testosterone levels significantly increased in both groups, supporting anabolic recovery mechanisms. DHEA-S exhibited a slight but non-significant increase, while the DHEA-S/cortisol ratio improved, suggesting enhanced stress resilience.ConclusionShort-term exposure to normobaric hypoxia induced significant hormonal adaptations, potentially aiding stress recovery in aviation professionals. These findings highlight the potential of controlled hypoxia as a non-pharmacological intervention for stress management in high-demand professions. Further research is needed to refine hypoxia protocols and assess long-term effects.